Black Hawk Down: A Story of Modern War - Bowden, Mark (New York Grove Press, 1999)
A Story of Modern War is based on a series of 29 articles written by journalist Mark Bowden for The Philadelphia Inquirer. He did extensive research in US Army records, interviewed participants from both sides of the conflict, reviewed footage recorded by observation aircraft, and listened to recordings of radio traffic. Before the book was published, Bowden's series had already begun to attract attention within the media.
Include Illustration
Keywords: Task force Ranger -- Operation Restore Hope